Geografia para todos: linguagem cartográfica tátil na sala de aula comum - Giehl Birão, Fabiana Cristina (2018)
In the current scenario of basic education, the training of teachers in classrooms after the policy of inclusive education stands out. These teachers are not always prepared to help students with disabilities and are facing challenge. With the teachers of Geography, it has not been different. In order to contribute to this teaching, and more specifically to the teaching of map reading, the present thesis has as general objective: analyze the effects of the educational program of introduction to the Tactile Cartographic Language, when applied in the context of the common classroom with students with visual impairment. The specific objectives are: identify if the teacher participating in the intervention had in its training access to subjects that deal with subjects and discussions about students with disabilities; verify the teacher's knowledge about tactile mapping; investigate the existence of possible proposals of cartographic education developed by the teacher regent with the participating students in the common classroom; ascertain the students' understanding of the reading of maps and their main elements (scale, legend, orientation, rose of the winds, title); investigate whether the students had already had contact with maps and tactile maps, and what is the students' knowledge about maps; describe the process of application of the educational program of introduction to the Tactile Cartographic Language. Therefore, qualitative exploratory research of a descriptive nature was carried out, characterized by an intervention. The research has the following number of Certificate of Presentation for Ethical Appraisal -CAAE, 54507116.4.0000.5504, and approval opinion N ° 1,543,820. Participants were: a teacher regent, a support teacher, two students with blindness and students without visual restrictions. The field research was developed with students from the fourth grade of elementary school I, following the procedures: identification of students with blindness who study in elementary school I; application of an open questionnaire with the participating teacher; conducting a survey with students; development of the educational program of introduction to the tactile cartographic language; conducting a new survey with students; and interview with the participating teacher. For this, the following data collection instruments were used: open questionnaire, survey, interview, field diary and intervention program. Data were submitted to descriptive analysis. The development of this study showed that the educational program of introduction to the tactile cartographic language and introduction to map reading can and should be developed by teachers with all the students in the common classroom. In addition, the lack of preparation of the teachers of the common teaching in front of the school inclusion of students with deficiency was evidenced.